2015
DOI: 10.3233/jad-150047
|View full text |Cite
|
Sign up to set email alerts
|

Voxel Level Survival Analysis of Grey Matter Volume and Incident Mild Cognitive Impairment or Alzheimer’s Disease

Abstract: The purpose of this study was to identify, at the voxel level, brain regions associated with the time to develop mild cognitive impairment (MCI) or Alzheimer’s disease (AD) from normal cognition. We analyzed incident MCI (n = 58) or AD (n = 151) in 292 cognitively normal participants in the Cardiovascular Health Study–Cognition Study (mean age = 79.2±3.6 years). We used segmented, modulated grey matter maps from 3D (spoiled gradient echo) MRI scans obtained in 1998/99 (with clinical follow-up through 2012) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 69 publications
4
29
0
Order By: Relevance
“…The113 participants with dementia met the criteria for dementia based on standard diagnostic criteria (see Methods section) and had both cognitive changes from baseline and disability related to their cognitive changes. They also differed from the normals on brain MRI, especially hippocampal volume and ventricular size [49]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The113 participants with dementia met the criteria for dementia based on standard diagnostic criteria (see Methods section) and had both cognitive changes from baseline and disability related to their cognitive changes. They also differed from the normals on brain MRI, especially hippocampal volume and ventricular size [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Lower hippocampal volume and higher ventricular grade, a marker of brain ‘atrophy’, were determinants of dementia in the CHS-CS [49]. We have previously reported that specific volumetric brain loss evaluated by Voxel-based morphometry was associated with time to both MCI and dementia in the CHS-CS [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is one of the first and most severely affected areas (Braak and Braak, 1997) and the memory loss characteristic of AD is generally thought to be due to neuronal degeneration in the hippocampus (Carli et al, 1997). Although there are some morphological changes that occur in the hippocampus as a result of normal aging, numerous studies have demonstrated particular pathological alterations associated specifically with AD (Ohnishi et al, 2001;Salat et al, 2001;Zeifman et al, 2014). Degradation in the cortices and hippocampus is characterized by a gradual decline in volume of gray matter (Irish et al, 2013;Möller et al, 2013;Ohnishi et al, 2001;Salat et al, 2011).…”
Section: Alzheimer's Diseasementioning
confidence: 97%
“…However, other brain regions may also be valuable for the prediction of progression, as indicated by voxel-based morphometry studies [ 13 15 ]. Two previous studies have used hypothesis-free voxel-level survival analyses to show that decreased gray matter in the medial temporal lobe and posterior cingulate cortex can predict time to conversion to AD-type dementia in nondemented subjects [ 16 , 17 ]. However, it is still unclear whether such predictive atrophy patterns are specific for amyloid pathology.…”
Section: Introductionmentioning
confidence: 99%